Investigation of Hydrogel Application on the Culture of Beans to Optimie Water Resource and Productivity - D.P. Silva; A.A.A. Pozza; B.S. Leite; S.A.F. Leite (Chemical Engineering Transactions, 2012)
Hydrogels are cross-linked polymers capable to absorb a great amount of water. Due to some of their properties such as hydrophilicity, high swelling capacity, lack of toxicity and controlled release, the applications on agriculture have been suggested for these polymers. Since most of the hydro resources used for human beings are destined for agriculture proposes, studies focused on the development of technologies to optimise the use of water turns out to be essentially important. Based on the subjects above, the goal of this research is to analyse the water absorption capacity of a commercial hydrogel (Stockosorb®) and to investigate if its use can improve the development of the culture of Phaseolus vulgaris beans. Firstly, the capacity of this hydrogel to absorb water was analyzed using gravimetric methods. Moreover, a randomized experimental design was used to investigate the hydrogel efficiency on the bean culture. Besides the control (soil with no amendments), two different concentrations of hydrogel were added to the pots and five levels of irrigation were applied to the experiment. The parameters height, amount of nodes, internodes and bean pods were recorded at weekly intervals to evaluate the growth of the plants. At the end of the experiment, dry weights of leaves, stems and roots and the productivity were also evaluated. In the first experiment it was observed that the hydrogel could absorb a great amount of water (more than 200 times its own initial weight). Also the results of the culture beans shown the addition of hydrogel to the soil was efficient to the growth of the plants and to the productivity. This research presented relevant agronomical and environmental results since it proves the efficiency of the use of the hydrogel Stockosorb® on the culture of Phaseolus vulgaris beans.